Праліси та старовікові ліси Українських Карпат: геопросторовий аналіз структури та чинників - Смалійчук, А. Д. (Київський національний університет імені Тараса Шевченка, 2017)
У статті виконано комплексний геопросторовий аналіз первинних природних лісів Українських Карпат, ідентифікованих згідно критеріїв та індикаторів визначених Карпатською конвенцією. Загалом площа таких лісів становить майже 80 тис. га, більша частина з яких є буковими. Аналіз просторових чинників поширення старовікових лісів та пралісів виконано з використанням моделі логістичної регресії. Його результати вказують на відсутність одного чи кількох визначальних чинників у геопросторовому розподілі цих лісів. Наявність збережених первинних природних лісів у широкому діапазоні умов місцезростань уможливлює їх використання в якості еталонів для реконструкції первинного стану біотичного компоненту геоекоситем чи ПТК, що є важливим завданням в умовах швидких глобальних кліматичних змін.

The paper deals with comprehensive geospatial analysis of primary natural forests of Ukrainian Carpathians, which has been identified in compliance with indicators and criteria defined by Carpathian Convention. On the beginning of 2017 the total area of such forests estimates as ca. 80,000 ha, 57% of which is virgin forests. Beech forests dominate, comprising over 55%, followed by spruce stands (ca. 33%) out of all identified primary natural forests. Virgin and old-growth forests can be found from foothill areas, mainly oak and alder stands, to sub-alpine belt, where dwarf pine and cedar pine stands are abundant. Our results suggest almost uniform distribution of all forests irrespectively to tree composition by slope indicator within the range 15 to 22 degrees. Mainly primary natural forests were found within mesoecoregions of “dissected lifted middle mountains” orographic class. Virgin forests are, in general, more remnants from both settlements and paved roads that remnants of old-growth forests. Logistic regression model was used in order to investigate spatial determinants of primary natural forests. We pre-selected seven determinants to build our model, namely: elevation, slope, aspect, distance to settlements, distance to roads, population density, and distance to forest edge. Only five of them was included to final model, aspect and slope of which showed the most influence on occurrence of primary natural forests. Underlying drivers, as land use history and former and present natural protection management, should be also considered for analysis of pattern of these forests. Identified virgin and old-growth forests can be the essential for understanding of potential natural vegetation as a component of geoecosystems. This may be crucial in the time of recent rapid climate change.
Virgin and old-growth forests of Ukrainian Carpathians: geospatial analysis of pattern and determinants
Keywords: первинні природні ліси; оверлейний аналіз; логістична регресія; просторові чинники; Українські Карпати; primary natural forests; overlay analysis; logistic regression; spatial determinants; Ukrainian Carpathians